Ginsenosides Rb2 and Rd2 isolated from Panax notoginseng flowers attenuate platelet function through P2Y12-mediated cAMP/PKA and PI3K/Akt/Erk1/2 signaling. Issue 13 (27th May 2021) - Zuo, Xiao; Li, Qing; Ya, Fuli; Ma, Li-Juan; Tian, Zezhong; Zhao, Mingzhu; Fan, Die; Zhao, Yimin; Mao, Yu-Heng; Wan, Jian-Bo; Yang, Yan
Abstract : PNF-derived G-Rb2 and G-Rd2 inhibited ADP-induced human platelet hyperactivity by modulating P2Y12 -mediated signaling, including up-regulating cAMP/PKA signaling and down-regulating PI3K/Akt/Erk1/2 pathways, which may inhibit thrombus formation. Abstract : Saponins derived from Panax notoginseng root are widely used as herbal medicines and dietary supplements due to their wide range of health benefits. However, the effects of those from Panax notoginseng flowers (PNF) on platelet function and thrombus formation remain largely unknown. Using a series of platelet function assays, we found that G-Rb2 and G-Rd2, among the ten PNF saponin monomers, significantly inhibited human platelet aggregation and activation induced by adenosine diphosphate (ADP) in vitro . The 50% inhibitory concentration (IC50 ) of G-Rb2 and G-Rd2 against ADP-induced platelet aggregation was 85.5 ± 4.5 μg mL −1 and 51.4 ± 4.6 μg mL −1, respectively. Mechanistically, G-Rb2 and G-Rd2 could effectively modulate platelet P2Y12 -mediated signaling by up-regulating cAMP/PKA signaling and down-regulating PI3K/Akt/Erk1/2 signaling pathways. Co-incubation of the P2Y12 antagonist cangrelor with either G-Rb2 or G-Rd2 did not show significant additive inhibitory effects. G-Rb2 and G-Rd2 also substantially suppressed thrombus growth in a FeCl3 -induced murine arteriole thrombosis model in vivo . Interestingly, G-Rd2 generally exhibited more potent inhibitory effects on platelet function and thrombus formation than G-Rb2. Thus, our data suggest that PNF-derived G-Rb2 and G-Rd2 effectively attenuate platelet hyperactivity through modulating signaling pathways downstream of P2Y12, which indicates G-Rb2 and G-Rd2 may play important preventive roles in thrombotic diseases.